Forkhead box protein 3+ regulatory T cells and Helios+ subset in perinatally acquired HIV. (April 2015) - Degaffe, G.; Zakhour, R.; Zhang, W.; Contreras, G. A.; Bell, C. S.; Rodriguez, G.; Del Bianco, G.; Pérez, N.; Benjamins, L. J.; Murphy, J. R.; Heresi, G. P.; Tran, D. Q.
Summary Forkhead box protein 3 (FoxP3)+ regulatory T cells (Tregs) are important not only in regulating the development of autoimmune conditions, but also in chronic infectious diseases. Given their cardinal function in suppressing immune activation, research has focused upon whether they play a detrimental role in chronic infections, particularly HIV. While the role of Tregs in HIV has been investigated intensively, it remains an unresolved topic. However, it is generally accepted that Tregs are susceptible to HIV infection and are preferentially preserved over conventional CD4+ T cells. It is unknown whether the peripheral‐induced or the thymic‐derived Tregs are more susceptible to HIV cytotoxicity. It has been recognized that Tregs can be segregated into two subsets based on Helios expression, with the vast majority being Helios+. This study examines the impact of HIV infection on total Tregs and their Helios subsets in a perinatal‐acquired HIV‐infected paediatric population. The finding indicates a selective expansion or survival of Tregs in association with CD4 depletion and increased viraemia. The Helios+ and Helios− subsets within Tregs appear to be equally affected. However, the Helios+ Tregs seem to be more preserved in patients with low CD4+ ≤ 25% and detectable plasma HIV RNA >20 copies/ml. In this group, the frequencies of Tregs are increased, but their numbers appear insufficient to restrain immune activation. In conclusion, our findings suggest that both Helios subsets of Tregs are susceptible to HIV infection and are preferentially preserved compared to conventional CD4+ T cells.